Parque lineal renaturalización Rio Chipalo (2021)
Urban growth has accelerated in intermediate cities, Ibagué presents problems due to this growth, there are many informal settlements that generate urban discontinuity and affect bodies of water, with the Chípalo river renaturalization linear park project, spaces are generated for different activities, improving appropriation of the natural resource benefiting the population.